Étude De La Gestion Des Déchets Hospitaliers Dans Les Structures Sanitaires De Référence De La Région Du Nord-Cameroun - Ndié, Justin; Yongsi, H. Blaise Nguendo (European Scientific Journal, ESJ, 2016)
Hospital wastes are solid, liquid or gaseous substances which are produced as a result of diagnostic or non-diagnostic health care procedures in health facilities. These wastes generated in health facilities constitute a risk for environmental pollution and a vector for the propagation of numerous pathologies. This study was aimed at analysing the determinants of the quality of hospital wastes management in health facilities in the North Region of Cameroon. It was a cross-sectional study carried out over a period of two months (1st of July to 31st August 2015) in 13 referral health facilities of the North Region of Cameroon. A census of 12 heads of referral health facilities out of the 13 projected was made using a standardised questionnaire, in which the key items were: the political and institutional organisation, the functioning of the hospital wastes management system, the human resources, materials and finances involved in the management of the hospital wastes. The quality of the scores was calculated using points attributed to keys indicators enabling the appreciation of the level of the quality of hospital wastes management. The results of this study showed that on the political/institutional level, 41.70% of health facilities did not have a hospital hygiene unit, 66.67% did not have a reference document and no health facilities produced any report on activities of hospital wastes management. In material resources, 50% of health facilities had at least one incinerator which is more or less functional, 91.70% of health facilities had a trash can despite their non-conformity. Concerning finances, 91.70% of health facilities did not receive funds from government for hospital wastes management. In total, 92% of health facilities had a poor quality of hospital wastes management. In general, this situation is justified by the inexistence of a hospital wastes management policy. Despite certain efforts, the quality of hospital wastes management in health facilities in the North Region of Cameroun remains low. The implementation of an operational plan which will take into account the national directives and the identified problems is necessary as it, will help in improving the quality of hospital wastes management in these health facilities.